(untitled) (Archaeologia Adriatica, 2008)
The article discusses the iconography of the polygonal silver reliquary from Novalja in the general context of the Early Christian iconography of the second half of the 4th and beginning of the 5th centuries. Particularly popular in this period were so-called Christocentric scenes, the main protagonists being Christ, Peter, and Paul, and not rarely they were joined by the entire twelve Apostles. The promotion of these themes is related to a specific historic moment in the Church whose iconography served as an instrument for spreading the truth about the one true ruler Jesus Christ and his kingdom, in contraposition to the imperial rulers and state. The central scene of the Novalja reliquary is "Traditio legis", which in Early Christian iconography was most highly represented in the period between 370 and 410 in all aspects of the arts. It was conjectured that it might have been depicted within the apse of Constantine’s St. Peter in the Vatican, whose iconography of that time has unfortunately remained unknown. "Traditio legis" in combination with the entire assembly of apostles most often appears on sarcophagi at the end of the 4th century and beginning of the 5th. Such an iconography appears in a reduced form on several reliquaries of the same period, including the reliquary from Novalja.